KONSEP KEADILAN RESTORATIF DALAM SISTEM PERADILAN PIDANA TERPADU - Rudini Hasyim Rado; Nurul Widhanita Y Badilla (Jurnal Restorative Justice, 2020)
Restorative justice has actually been known in the daily reality of even a local knowledge in a variety of customary law in Indonesia. Local wisdom which is hidden pearl that has been duly examined and modified again in order to shine again, illuminating the face of fading and darkness current law. Darkness law faces today due to the prevailing criminal justice system has not been fully integrated to ensure fairness (integrated justice), namely justice for perpetrators, justice for the victims, and justice for the people. This has pushed forward the concept â€œrestorative justice.â€ Seat restorative justice which is an implementation of the concept of diversion has been formulated even if still limited in the juvenile justice system and restorative justice can contribute in two ways or forms, forms of settlement out of the criminal justice process (traditional institutions of village/community institutions village) as well as the shape of the settlement as part of the integrated criminal justice system process (SPPT) through the investigator, public prosecutor, judge and prisons. Keywords: restorative justice; diversion; integrated criminal justice system.